Mine enemy grows older - King, Alexander (Simon & Schuster New York, 1958)
Alexander King, one of the first editors of Life magazine, a collaborator on plays with Clare Booth Luce, and a book illustrator, tells, among other things, of undergoing four "cures" for drug addiction in a ten-year period.
Autobiography
Keywords: King, Alexander -- 1900-1965; Autobiography